2021
DOI: 10.3390/rs13244962
|View full text |Cite
|
Sign up to set email alerts
|

Correcting Imprecise Object Locations for Training Object Detectors in Remote Sensing Applications

Abstract: Object detection on aerial and satellite imagery is an important tool for image analysis in remote sensing and has many areas of application. As modern object detectors require accurate annotations for training, manual and labor-intensive labeling is necessary. In situations where GPS coordinates for the objects of interest are already available, there is potential to avoid the cumbersome annotation process. Unfortunately, GPS coordinates are often not well-aligned with georectified imagery. These spatial erro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…This often results in imprecise bounding box labels. To address this challenge of noisy labels, recent works [24]- [27] have developed sophisticated training methods that typically require large amounts of data, computationally expensive optimization strategies and multiple additional objectives. In contrast InterAug works out of the box, without requiring any modifications to the training loop or the model architecture, and provides significantly robust detectors and is effective even under scarce training data scenarios.…”
Section: Related Workmentioning
confidence: 99%
“…This often results in imprecise bounding box labels. To address this challenge of noisy labels, recent works [24]- [27] have developed sophisticated training methods that typically require large amounts of data, computationally expensive optimization strategies and multiple additional objectives. In contrast InterAug works out of the box, without requiring any modifications to the training loop or the model architecture, and provides significantly robust detectors and is effective even under scarce training data scenarios.…”
Section: Related Workmentioning
confidence: 99%
“…vision background are not sure how to annotate high-quality boxes, while annotators without domain knowledge can also be difficult to annotate accurate object boxes. For example, recent wheat head detection challenge 1 that was hosted at the European Conference on Computer Vision (ECCV) workshop 2020 has shown that precise object bounding boxes are not easy to obtain, because in some domains the definition of the object is significantly different from generic objects in COCO, thus brings annotation ambiguities (Fig. 1).…”
Section: Fasterrcnn With Regression Uncertaintymentioning
confidence: 99%
“…Recently, learning object detectors with noisy data have gained a surge of interest, several approaches [1,5,25,47] have made attempted to tackle noisy annotations. These approaches often assume that the noise occurs both on category labels and bounding box annotations, and devise a disentangled architecture to learn object detectors.…”
Section: Fasterrcnn With Regression Uncertaintymentioning
confidence: 99%
See 1 more Smart Citation
“…Due to these practical challenges, the actual labels often deviate from the ideal value, which leads to labels that are inconsistent with the instances. Even though extensive works of deep learning techniques under class noise exist ( Li et al., 2020 ; Bernhard and Schubert, 2021 ; Mao et al., 2021 ; Xu et al., 2021 ), it mainly focuses on computer vision datasets such as MS-COCO ( Lin et al., 2014 ), PASCAL VOC ( Everingham et al., 2010 ), and ImageNet ( Deng et al., 2009 ) rather than domain-specific datasets. In some domains, the definition of an object is significantly different from generic objects in these typical datasets, thus bringing annotation ambiguities.…”
Section: Introductionmentioning
confidence: 99%